Paradolia Common Rhetorical Ianguage Used in Communication(Emoticons) - Sahera Abdel Wahed, Assi.Prof. Dr; Ziad Odeh Rabah, Assist. Lect. (lark, 2022)
The current paper discusses the scientific and technological development that shows the intellectual change in the pursuit of documenting human ideas and the circulation of knowledge through time and the search for new ways that would study the physiological and anthropological sciences and benefit from them in an attempt to understand the human spirit and evoke the state of non-verbal visual communication with the aim of documenting human thoughts and linking emotion with the visual image.Paradolia, the subject of the research, represents a starting point for the multiple approaches followed by the designer as a means of understanding the human condition and the state of perception, linking them to figurative forms and symbols, using them as a communicative translation of thoughts and emotions as a state of reduction, using a new language to communicate, and giving visual and functional symbols of expression that transcend the limits of time, place and differences. In languages and cultures. , The research problem was: Is pareidolia the common nonverbal language of speech used in social media?The importance of the research lies in shedding light on a phenomenon or concept (paradolia) and what can be benefited from and employed in the field of design. One of the most important results of the research is that emojis break the barrier of language isolation between different countries and peoples because this language is distinguished by the fact that it does not need well-known grammar rules.
Keywords: (Paradolia , Visual Discourse, Common Discourse, Usage)